Evaluation of Serum Triglyceride and TG/HDL-Cholesterol Ratio in Good and Poor Control Type-2 Diabetes Mellitus - Sultana, Dalia; Roy, Manindra Nath; Karmakar, Pijush; Zohora, Fatema Tuz; Hoque, Md Enamul; Sharna, Rawnok Jahan (Eastern Medical College Journal, 2024)
Introduction: Patients with type-2 diabetes have an increased prevalence of dyslipidemia, which contributes to their high risk of cardiovascular diseases. The mortality and morbidity are increased if there is poor glycemic control. Diabetic dyslipidemia is characterized by elevated TG levels, decreased HDL-C levels and increased levels of LDL-C. The aim of this study was to evaluate serum triglyceride and TG/HDL-cholesterol ratio in good and poor control type-2 diabetes mellitus. Methodology: The present study was carried out in departments of Biochemistry, Medicine and Endocrinology of Sir Salimullah Medical College and Mitford Hospital, Dhaka, Bangladesh between the periods of July 2020 to June 2021. By convenient sampling, a total of 50 subjects aged between 30-59 years were enrolled in this study. Study subjects were divided into 2 groups. Group-A included subjects with good glycemic control (n=25) and group-B included subjects with poor glycemic control (n=25). Results: The mean HbA1c level was significantly higher in poor glycemic group than good glycemic group (10.9±12.02% vs. 5.98±0.95%). The mean TG was 173.16±36.9 mg/dl in good glycemic control group and 219.4±70.32 mg/dl in poor glycemic group. There was significant difference in TG/HDL-C ratio in 2 groups. Serum triglyceride and TG/HDL-C ratio had positive correlation with HbA1c but was not significant. Conclusion: Poor glycemic control is associated with dyslipidemia in Type-2 Diabetes Mellitus. Eastern Med Coll J. July 2023; 8 (2): 24-28